Faktor-faktor yang berhubungan dengan kejadian Hipertensi primer pada masyarakat di wilayah kerja puskesmas rumbai pesisir - Raihan, Lailatun Najmi; -, Erwin -; Dewi, Ari Pristiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to determine the factors relating to the incident of primary hypertension in community of Rumbai Pesisir Community Health Center. This research was an analytical research using case control study approach. Samples were taken by using accidental sampling method which totaled 156 respondents. The analysis used univariate and bivariate analysis. This research is consist of 9 variables and based on the results of the chi-square test statistic can be concluded that there are five variables that showed a significant correlation, that is hereditary (p value = 0,000); smoking habit (p value = 0,006); activity/exercise (p value = 0,000); salt intake (p value = 0,001); stress (p value = 0,000). Meanwhile, there are 4 variables that showed no significant correlation, that is age (p value = 0,211); sex (p value = 0,436); alcohol consumption (p value = 0,050); body mass index (p value = 0,167). The results of this research recommends increasing the importance of a healthy lifestyle for the community and health education programs on healthy lifestyles by by staff of Puskesmas Rumbai Pesisir. Keywords : Related factors, Incident of primary hypertension, Community of Rumbai Pesisir Community Health Center